L1 (ARABIC) INTERFERENCE IN LEARNING L2 (ENGLISH): AN ANALYSIS OF ENGLISH SPELLING USED BY ARABIC SPEAKERS AT UNDERGRADUATE LEVEL - A CASE STUDY - Sameera Sultan Baloch (European Scientific Journal, ESJ, 2013)
The focus of this study is spelling mistakes done by undergraduate students while using letters b, p, e. The basic aim of this study is to analyse these spelling mistakes and observe how mother tongue (Arabic) interferes in the learning of second language (English) in terms of spellings. A list of more than 50 misspelt words was collected from students' written exams. It was observed that 'b' is replaced with 'p' in monosyllabic words if it appears in the beginning before 'o'. If 'p' is in the beginning of the words before consonant 'r' in polysyllabic words, it is replaced with 'b'. In another situation when 'p' is placed after 'm' in the middle of words, it is replaced with 'b'. The case of substitution of 'p' with 'b' and vice versa is observed mostly in nouns. Omission and addition of 'e' in the final position occur because students may not find such example in their mother tongue and also they do not find spelling rules for 'e' at the final position of words in English.